Selective Herbicide Combinations Sustain Early Eucalyptus pellita Growth and Soil Microbial Abundance During Plantation Land Preparation in South Sumatra - Prebiton Yusef; Ahmad Muslim; Adipati Napoleon (Sriwijaya Journal of Environment, 2026)
Background: Herbicide application during land preparation is routine in tropical industrial plantation forestry, yet its simultaneous effects on soil biology, weed cover, and tree growth are rarely evaluated together. Objective: This study assessed the effects of herbicide combinations applied during land preparation on weed cover, early growth of Eucalyptus pellita (height and stem diameter), and total soil microbial abundance at PT Musi Hutan Persada, Muara Enim, South Sumatra, Indonesia, as an implementation of IFCC Indicator 7.2.8 on minimising chemical pesticide use. Methods: A Completely Randomized Design with four treatments and four replications (16 plots of 360 m²) compared P1 (control), P2 (indaziflam+iodosulfuron, 250 g ha⁻¹), P3 (glyphosate 3 L ha⁻¹ + indaziflam+iodosulfuron), and P4 (glyphosate 3 L ha⁻¹ + metsulfuron-methyl 300 g ha⁻¹ + indaziflam+iodosulfuron), analysed by one-way ANOVA with η² effect sizes, LSD separation, Pearson correlation, and principal component analysis. Results: Herbicide treatment significantly reduced weed cover (F(3,12)=18.42, p<0.001, η²=0.82), with suppression of 27.9%, 45.9%, and 68.1% in P2, P3, and P4, but did not significantly affect height, stem diameter, or microbial abundance (all p>0.05). Microbial abundance stayed about four orders of magnitude above the 10² CFU g⁻¹ degradation threshold of Regulation No. 07/2006, and all plots were classified as not degraded. Conclusion: Selective, well-timed herbicide combinations can control weeds effectively without compromising early E. pellita growth or soil microbial abundance, supporting sustainable plantation management under IFCC Indicator 7.2.8.